Pengaruh Subsitusi Tepung Biji Nangka dan Tepung Ikan Lemuru terhadap Mutu Fisik dan Analisis Kandungan Zat Gizi (Protein, Kalsium, Zinc, Fe) Cookies - Grace Hanna Ully Gultom; Oslida Martony (NUTRIENT, 2021)
This study aims to determine the effect of substitution of jackfruit seed flour and lemuru fish meal on physical quality and analysis of nutritional content (Protein, Calcium, Zinc, Fe) in cookies. This research method used experimental method with completely randomized design (CRD) treatment with 3 treatments and 2 repetitions. The results of the analysis of jackfruit and lemuru seed cookies per 100 grams contain 41.25 grams of Protein, 261 mg of Calcium, 75 mg of Zinc and 4 mg of Fe. In conclusion, jackfruit and lemuru seed cookies can be used as PMT for school children to meet the needs of protein, carbohydrates and calcium. Keywords: Cookies, Supplementary Food, Jackfruit Seed Flour, Lemuru Fish Flour, Wheat Flour